Molluscan shelltish resources of India - An overview - Narasimham, K A; Kripa, V; Balan, K (Indian Journal of Fisheries, 2011)
In recent times the molluscan shellfishare fast emerging as an importantcomponent in the marine fisheries of thecountry. Cephalopods are much sought afterin the export trade. Their production trendis showing spectacular growth rate. Theedible oysters, mussels and clams arenutritious sea foods with considerable exportpotential.